PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA DOSEN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL ANTARA (STUDI KASUS PADA PTS DI SURAKARTA) - Elia Ardyan Elia; Budi Istiyanto Budi (Derivatif : Jurnal Manajemen, 2016)
ABSTRACT       This research aims to know that leadership style, motivation and organization culture can influence the lecturer performance through organizational commitment, besides, to be able to be reference for the next research having almost the same discussion.The research is conducted using primary data that is questionnaire distributed to the respondent as the sample. The sample of this research is the lecturers in the private colleges in Surakarta area. The questionnaire distribution uses the sample counted 50 respondents for certificated lecturers because it is based on what will be discussed in this research.The questionnaire is tested its validity and reliability. The questionnaire which is distributed from the validity and reliability test result produces valid and reliable questionnaire. For the model used in the research is done classical assumption test consisting multi colonearity, heterosdesticity, autocorrelation, and normality.Doubled regression test is done in two stages they are to test causal regression I and causal regression II. Causal regression I is to know the influence of leadership style, motivation and organization culture toward organizational commitment. Causal regression II is to test the influence of leadership style, motivation, organization culture and organizational commitment toward the performance with the purpose to know the direct influence of variable of leadership style, motivation and organization culture toward the performance, also for indirect influence if there must be organizational commitment among those variables.The result and discussion gotten from causal regression I test knows that leadership style and lecturer motivation influence the organizational commitment, while organization culture does not influence the organizational commitment. Causal regression II knows that only motivation influences the lecturer performance, but if the motivation is not directly to the performance yet must be through organizational commitment so the motivation does not have influence the performance. For the leadership style and organization culture variable either directly or indirectly do not have influence the performance, and also with the organizational commitment.The result of the research will be used as the enrichment material and included into reputable online journal. Suggestion for the next research is expected having sample which is broader its scope of area cooperate with parties supporting the next research like Kopertis (Private Colleges Association) Keyword :  leadership style, organization culture, motivation, performance, organizational                   commitment